2021
DOI: 10.1111/eve.13432
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of behaviour during tacking‐up and mounting in ridden sports and leisure horses

Abstract: Such behaviours may be exhibited in anticipation of musculoskeletal pain during ridden exercise, which may be associated with ill-fitting tack in some horses.• Owners need to be made aware that these behaviours are not normal and may be a manifestation of underlying problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…In a prospective observational study of a convenience sample of 193 sports and leisure horses, in regular work and presumed by their owners to be working comfortably, which were observed during mounting and ridden exercise on a single occasion, two horses pronked repeatedly when moving off after mounting (Dyson et al . 2022). In a subset of 148 of these horses with video footage available for retrospective analysis of ridden performance, bucking was observed in one horse (0.7%).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective observational study of a convenience sample of 193 sports and leisure horses, in regular work and presumed by their owners to be working comfortably, which were observed during mounting and ridden exercise on a single occasion, two horses pronked repeatedly when moving off after mounting (Dyson et al . 2022). In a subset of 148 of these horses with video footage available for retrospective analysis of ridden performance, bucking was observed in one horse (0.7%).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Then progress to placement of the saddle, repeating the slow tightening of the girth and moving forwards after each tightening and also observing the horse’s behaviour (Dyson et al . 2021).…”
Section: Clinical Investigation Of Bucking Behaviourmentioning
confidence: 99%
“…Objective assessment of acute pain in equids has been studied extensively in the last few decades [ 7 , 8 , 9 ], and both composite and facial expression-based pain scales have proven useful in horses with different types of acute pain [ 6 , 10 ]. Pain assessment has also been described in ridden horses [ 11 ] and in horses during tacking-up and mounting [ 12 ]. Moreover, in donkeys, a recent study has shown that composite and facial expression-based pain scales can be successfully used [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypersensitivity in the girth region may be implicated (Van Iwaarden et al 2012;Bowen et al 2017). In some horses with gastric ulceration treated using omeprazole with or without sucralfate, abnormal behaviour during tacking-up has resolved (Millares-Ramirez and Le Jeune 2019; Dyson et al 2020c). Muscle compression by the saddle may also induce changes in behaviour (Van Iwaarden et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle compression by the saddle may also induce changes in behaviour (Van Iwaarden et al 2012). However, a recent observational study documented that in a proportion of horses more abnormal behaviour was seen while the bridle was put on than when the saddle was positioned and the girth was tightened (Dyson et al 2020c). It has been suggested that the use of a tight crank cavesson noseband may inhibit normal facial movements during tacking-up and that this may be associated with stress, as reflected by an increase in heart rate compared with use of a less restrictive noseband (Fenner et al 2016).…”
Section: Introductionmentioning
confidence: 99%